Integrasi Psikologi Barat dan Islam: Sebuah Literature Review tentang Epistemologi, Pendidikan, dan Konseling - Hamidah Hamidah; Mu’alimin Mu’alimin; Mukffan Mukffan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The integration of Western psychology and Islamic perspectives has become an important issue in the development of contemporary science and education. The rapid advancement of modern psychology calls for a synthesis with the epistemological framework of Islam to be more contextual in addressing academic and practical needs, particularly in the fields of education, counseling, and character development. This article aims to answer the research question: How is the trend of integration between Western psychology and Islamic perspectives in the current literature, and what are the implications for Islamic education theory and practice? This study uses a literature review method with a qualitative approach. Articles were collected via Google Scholar and the Publish or Perish application using the keywords